Social Roles of the Teacher in Militarized Educational Institution - Indriksons, Alens (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In our daily life, in society we are fulfilling a variety of roles. Teacher in educational institution has a number of roles which are performed to achieve the objectives of the educational process. In contradistinction to vocational education institutions, militarized educational institutions train staff for performance of specific tasks. The main task is to make the personnel ready for practical service. Militarized educational institutions are working on the basis of principle of one man management. Teacher in such institutions is an official with the service rank and in educational process he performs specific roles as a result of service relationship. The present paper discovers the nature of specific roles and how they effect achieving the goal in militarized educational institution.